PENGEMBANGAN NILAI-NILAI SPIRITUAL BERBASIS PESANTREN KILAT (Studi Pengembangan Model Pembelajaran Pesantren Kilat yang Inovatif dan Efektif untuk Siswa Sekolah Lanjutan Tingkat Atas) - Muhammad Ihsan Dacholfany; Ni Putu Ayu Kartika Sari Dewi; Bambang Ismaya; Suhardi Suhardi; Ratih Kusumastuti (Sekolah Tinggi Agama Islam Al Hidayah, 2012)
This research was carried out based on the notion that there was a low awareness of religious conducts especially among senior high school students. As an effort to increase this awareness, during the holly month of Ramadhan many high school in big cities held short religious teaching program known as pesantren kilat. These programs were also held as extra-curricular activities during Ramadhan holiday. However, most programs were not managed so that their contribution to increase students’ awareness of religious conducts was not significant.The study was focused on developing an effective and innovative pesantren kilat learning model for senior high school students. Particular emphasis was given on the development of program objectives, materials, methods, teaching and evaluation technique, interaction patterns and dissemination method of the model. A developmental research approach with main stages of actual model description, hypothetical model development, experiment, hypothetical model revision, and dissemination method design, was used. Data were obtained from participants of pesantren kilat held in SMU Taman Islam and pesantren kilat organizers in SMUN V, SMU Bina Bangsa Sejahtera and SMU Ibnu 'Aqil. All respondents were selected purposively. A qualitative method was used to test the model invention and design and quantitative method to test the effectiveness of the experiment.It was found from the observation that the implementation of pesantren kilat in four selected SMUs did not meet the criteria of good pesantren kilat program. The programs were only considered as extra lessons of Islamic Education given as extra-curricular activities. An effective pesantren kilat model will exist if the relation within teacher and students is like that of kyai and santri. Therefore, a learning model was introduced. The model was aimed at increasing the knowledge and understanding of Islamic values as well as increasing the knowledge and practice of daily rituals. The courses covered materials related to individual obligation (fardhu ‘ain). The teaching method and techniques included discussion (mudzakarah) and field practice. The evaluation technique was directed toward the recognition of students’ knowledge and skills as a means of motivating them to learn Islamic values. In addition, the program was conducted in a participatory learning.Based on the results of quantitative and qualitative analyses, it was found that the model showed significant effectiveness. It was concluded that with its limitations, the learning model proposed was still applicable. Other learning models in pesantren kilat such as a boarding system deserve further investigation.